Odpowiedzi

2010-01-13T16:20:59+01:00
X+y=60
12x+1,6y=4800+16x-16y

x=-y+60
12*(-y+60)+1,6=4800+16*(-y+60)-16y
-12+-720+1,6y=4800+-16y+-960+-16y
-10,4y+-720=4800+-960
-10,4y+-720=3840
-10,4y=3840-720
-10,4y=3120/:-10,4
y=300

x=-y+60
x=-300+60
x=-240

{y=300
{x=-240
2010-01-13T16:24:26+01:00
X + y = 60
12x + 1,6y = 4800 + 16x - 16y / : 4

x = 60 - y
12 ( 60 -y ) + 1,6 y = 4800 + 16 (60 - y) - 16y

x = 60 - y
720 - 12y + 1,6y = 4800 + 960 - 16y - 16y

x = 60 - y
- 12y + 32y + 1,6 y = 5040

x = 60 - y
21,6 y = 5040 / : 21,6


x = 60 - y
y = 233,33

x = 60 - 233,33
y = 233,33

x = - 173,33
y = 233,33

2010-01-13T16:46:01+01:00

x+y=60
12x+1,6y=4800+ 6x-16y /: 4

x = 60 - y
12 ( 60 -y ) + 1,6 y = 4800 + 16 (60 - y) - 16y

x = 60 - y
720 - 12y + 1,6y = 4800 + 960 - 16y - 16y

x = 60 - y
- 12y + 32y + 1,6 y = 5040

x = 60 - y
21,6 y = 5040 / : 21,6

x = 60 - y
y = 233,33

x = - 173,33
y = 233,33

Mam nadzieje, że pomogłam...
Pozdrawiam...